Associations Between Ambient Particle Radioactivity and Blood Pressure: The NAS (Normative Aging Study). Issue 6 (15th March 2018) - Nyhan, Marguerite M.; Coull, Brent A.; Blomberg, Annelise J.; Vieira, Carol L.Z.; Garshick, Eric; Aba, Abdulaziz; Vokonas, Pantel; Gold, Diane R.; Schwartz, Joel; Koutrakis, Petros
Abstract : Background: The cardiovascular effects of low‐level environmental radiation exposures are poorly understood. Although particulate matter (PM) has been linked to cardiovascular morbidity and mortality, and elevated blood pressure (BP), the properties promoting its toxicity remain uncertain. Addressing a knowledge gap, we evaluated whether BP increased with higher exposures to radioactive components of ambient PM, herein referred to as particle radioactivity (PR). Methods and Results: We performed a repeated‐measures analysis of 852 men to examine associations between PR exposure and BP using mixed‐effects regression models. As a surrogate for PR, we used gross β activity, measured by the US Environmental Protection Agency's radiation monitoring network. Higher PR exposure was associated with increases in both diastolic BP and systolic BP, for exposures from 1 to 28 days. An interquartile range increase in 28‐day PR exposure was associated with a 2.95–mm Hg increase in diastolic BP (95% confidence interval, 2.25–3.66; P <0.001) and a 3.94–mm Hg increase in systolic BP (95% confidence interval, 2.62–5.27; P <0.001). For models including both PR and PM ≤2.5 µm, the PR‐BP associations remained stable and significant. For models including PR and black carbon or PR and particle number, the PR‐BP associations were attenuated; however, they remained significant for many exposure durations. Conclusions: This is the first study to demonstrate the potential adverse effects of PR on both systolic and diastolic BPs. These were independent and similar in magnitude to those of PM ≤2.5 µm, black carbon, and particle number. Understanding the effects of particle‐bound radionuclide exposures on BP may have important implications for environmental and public health policy.